2019
DOI: 10.1186/s13765-019-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

A 1,1′-biuracil from Epidermidibacterium keratini EPI-7 shows anti-aging effects on human dermal fibroblasts

Abstract: Our previous study we isolated novel bacterial stain, Epidermidibacterium keratini, called EPI-7 T from skin samples. Repeated column separation yielded one new pyrimidine compound, 1,1′-biuracil, from EPI-7 T culture solutions grown in R2A medium. Its chemical structure was determined based on spectroscopic data, IR, FAB/MS, and NMR. And 1,1′-biuracil and EPI-7 T culture solutions showed regulating effects of anti-aging associated mRNA expressions in UV-irradiated fibroblasts without toxicity in Hs68 cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The instruments and chemicals used in these experiments were prepared according to previous studies [10][11][12].…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…The instruments and chemicals used in these experiments were prepared according to previous studies [10][11][12].…”
Section: General Experimental Proceduresmentioning
confidence: 99%
“…A previous study revealed that a pyrimidine compound from a bacterial strain, EPI-7T, had an anti-aging effect on human dermal fibroblasts (HDFs) 23 . Therefore, we hypothesized that the abundant Streptococcus facial colonies could secrete compounds related to skin aging.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorbents for CC and TLC analysis were the same as those previously used . Melting point, optical rotation, IR, ECD, NMR (600 MHz), and HRFABMS measurements were performed as previously reported …”
Section: Methodsmentioning
confidence: 99%